Digital governance in rural Chengdu, China: Its potential for social-ecological resilience - Wu, Shuang; Abramson, Daniel Benjamin; Zhong, Bo (Frontiers in Sustainable Cities, 2022)
In this study, we echo the call from the UN to interpret Sustainable Development Goals (SDGs) in their regional context—in this case, the linpan (wooded lot) landscape of the Chengdu Plain, in Sichuan, China, where the shocks and stresses of recent, rapid administrative-economic urbanization are testing the resilience of some of the world's most sustainably productive and long- and densely-settled agrarian environments. In recent years, fine-grained information and communications technology (ICT) governance tools in Chengdu, such as “grid management”, present opportunities to sustain and scale up the collection of data necessary to validate and refine indicators of landscape resilience, and use them to regulate development, in accordance with SDG goal 11 to enhance legislation, governance, and capacity via information gathering and sharing. ICT-based governance in combination with traditional place-based knowledge can play a critical role in ensuring the resilience of urban-rural co-development. To realize this potential, however, ICT-enabled governance needs to incorporate greater transparency and more local feedback loops and enable greater participation from older farmers and women, to inform household and community-level land-use choices and initiatives. It also needs to link regulatory functions with marketing and pricing functions so that farmers may benefit from the sustainable practices they are encouraged to adopt.